Gerakan Islam Transnasional: Sebuah Nomenklatur, Sejarah dan Pengaruhnya di Indonesia - Aksa Aksa (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2017)
Transnational Islamic movement is a terminology that belongs in the new academic study. The term has become a ' nomenclature ' is generally understood as an ideology that crosses state boundaries (nation state). The emergence of transnational Islamic movement's lively lately is part of an Islamic revival and renewal of an era that grew in the Middle East since the 18th century. The post-war collapse of the Caliphate based in Ottoman Turkey in 1924, the movement has found the right momentum by forming new forces in conducting resistance against colonialism and imperialism of the West. Presence of transnational Islamic movement in Indonesia is part of the revivalism Islamic movement in the Middle East that directly make effect against the pattern of Islam in Indonesia. Transmission lines the ideas of this movement through the social movements, education and publications